Tax Fraud in International Trade: Analysis of Driving Factors and Economic Implications - Nanlohy, Yehezkiel Benaya; Rohmansyah, Muhammad Nur; Hwihanus (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to find out what are the driving factors and economic implications of tax fraud in international trade. The research method used in this research is the meta-analysis method. This research uses data from articles available in full text form. Data sources were searched and taken from Researchgate, Sciencedirect, Emerald, and Taylor And Francis. The subject of this research is tax fraud in international trade while the object is an article. Of the 5 articles that have been studied by researchers, they discuss the driving factors and economic implications of tax fraud in international trade. Then the article is reviewed using analytical techniques, looking for driving factors and economic implications among several literatures and drawing conclusions. The results of the analysis from these 5 journals show that there are several driving factors and economic implications in the occurrence of tax fraud in international trade. Driving factors and economic implications include the role of tax havens, invoice and VAT errors, ghost companies, changes in company structure, tax avoidance and tax rates. These five factors state that they influence the occurrence of tax fraud in international trade activities.